6th Poly Royal (1938)
Various footage of Poly Royal Events [00:00:15] Opens with view of American flag [00:00:21] "A country Fair on a College Campus depicting Poly's Progress" [00:00:27] People viewing cattle [00:00:58] "The Chief Julian A McPhee Opens Activities" [00:01:03] Band Performing [00:01:22] "Arnold Wirtz President of Student body Carries on!" [00:01:34] "Oscar Hucksinger Welcomes the Crowd!" [00:01:41] "A.G. Rinn Regional Supervisor â€" Sacramento Valley â€" Says Hello!" [00:01:53] "W.S. Guilford Speaks for Farm Credit Admin." [00:02:00] "Alex McDonald the Official Livestock Judges!" [00:02:07] "Leo Fitzgerald Introduces the Queen and Queen Candidates" [00:02:28] "Potato Race and Steer Riding" [00:04:31] "Gilbert Jackson twirls a Mean Rope!" [00:05:14] "Everyone Leaves for Lunch!" [00:05:23] "Department Display a Diversity of Demonstrations" [00:05:28] "Agricultural Mechanics!" [00:06:12] "Aeronautics" [00:06:40] "Electrical Industries" [00:07:07] "Air Conditioning" [00:07:26] "Fruits!" [00:07:59] "Agricultural Inspection puts on a Skit!" [00:08:20] "Landscaping" [00:09:50] "Poultry" [00:10:02] "Raymond Nelson Judges Poultry" [00:10:17] "A Class of Jersey Heiter" [00:10:38] "Alex McDonald Action!" [00:11:00] "Champion Hog Class!" [00:11:08] "Adult Farmers Judge Livestock!" [00:12:35] Milking Competition with Cecil â€˜Spud' Evansini and Harold Tannis [00:13:55] "'Hub' Hollister Rotary the Winner" [00:14:29] "Mrs. King make Coffee" [00:14:44] "Mr. Hollenberg and Crew Barbecue the Meat" [00:15:38] "Chris Jespersen Likes His Steak" [00:15:51] Cal Poly Musicians [00:16:00] Baseball Game Cal Poly vs. Santa Maria J.C. [00:16:38] "Parade of the Champions" [00:17:25] Bagpipe Player Performs [00:17:46] Women Hammering Nails [00:18:05] "Capt. A.H. Hardy and Party Demonstrate Clever Shooting" Kids and woman shoot guns [00:18:45] "Marcel Lavous presents Trophies" [00:19:21] "Don McMillan the Sage of Shandor says Au Revoir" [00:19:40] Sundown [00:19:45] Credits